Erratum: "Search for dark matter annihilation signals from the Fornax Galaxy Cluster with H.E.S.S." - Medina, Maria Clementina (2014)
In the article by Abramowski et al. (2012), H.E.S.S. observations of the Fornax galaxy cluster were used to produce exclusion limits on a dark matter (DM) annihilation γ -ray signal. Upper limits on the velocity-weighted annihilation cross section (σ v) as a function of the DM particle mass were computed. Constraints were derived for different DM particle models, such as those arising from supersymmetric models, and various annihilation final states were considered. Here we report on three independent problems identified with some of the figures and DM annihilation spectra used in that article